Modification and Application of Dye Extract from Tectona Grandis on Cotton Fabric - Joshua, Y; Ago, M. A.; Alheri, A.; Ujah, F.R (African Journal of Sciences and Traditional Medicine, 2024)
The natural dye was extracted from Tectona grandis using a soxhlet extractor, and a percentage yield of 16.84% was obtained. The color of the dye extract is maroon, and after the dye extract was modified, the color changed to brown. The modified dye was characterized using FTIR, AMF, and UV-visible spectroscopy. The results of the FTIR suggested the presence of C-H, C=C, C=O, N-H, C-O-C, C-Cl, and C-Br functional groups. The AFM suggests that the area roughness is 629.9 nm in the 25μm×25μm scan area. The UV shows a maximum wavelength of 581 nm with an absorbance of 0.074. The chromophore of the modified dye extract is -N=N- and C=O. The modified dye was applied to the cotton fabrics. The color fastness to washing shows that 3–4 and 4 were experienced for color change and staining, respectively, while the color fastness to rubbing shows that 4-5 and 4 were experienced for dry and wet rubbing, respectively. The outcome of color fastness shows that the modified dye has a good affinity to remain on the fabric. We therefore recommend the use of different kinds of mordants to improve the affinity of cotton fabric.